1999
DOI: 10.1016/s0016-5085(99)70449-x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of Ras-transformed epithelial cell growth is linked to down-regulation of epidermal growth factor–related peptides

Abstract: These data suggest that one mechanism by which FTIs inhibit growth of H-Ras-transformed epithelial cells is by reducing Ras-induced EGFR ligand production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Our results showed also here that AR stimulated the IGF1-R, which in turn induced the release of AR, an amplification phenomenon that could also explain the high levels of AR secreted by H358 cells. Furthermore, H358 cells express a mutated constitutively active Ras protein (59), and Ras activation has been shown to increase the production of EGF-related peptides (60,61). Accordingly, H322 cells, which did not secrete AR, express a wild-type Ras protein (59).…”
Section: Ar and Igf1 Inhibit Serum Deprivation Apoptosis Of H358 And mentioning
confidence: 99%
“…Our results showed also here that AR stimulated the IGF1-R, which in turn induced the release of AR, an amplification phenomenon that could also explain the high levels of AR secreted by H358 cells. Furthermore, H358 cells express a mutated constitutively active Ras protein (59), and Ras activation has been shown to increase the production of EGF-related peptides (60,61). Accordingly, H322 cells, which did not secrete AR, express a wild-type Ras protein (59).…”
Section: Ar and Igf1 Inhibit Serum Deprivation Apoptosis Of H358 And mentioning
confidence: 99%
“…Moreover, Ras signaling through mitogen-activated protein kinase is an important regulator of the production of EGFR ligands, such as transforming growth factor a (TGFa) and amphiregulin (AREG), and contributes through this mechanism to the autocrine activation of EGFR and its downstream signaling cascades (14). For H-RAS -mutated tumor cells, an elevated production of the EGFR ligands TGFa and AREG has been reported (15,16). Because EGFR signaling is a major mechanism in the control of cell proliferation and survival, a Ras-dependent autocrine loop of EGFR activation may contribute to cell growth, as described for tumor cells overexpressing mutated H-RAS and K-RAS (17).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is well known that FTIs block the growth of a variety of tumor cells without Ras activation (21,22). It is possible that this occurs because activated receptor tyrosine kinases constitutively activate Ras that is then inhibited by FTIs; alternatively, FTIs may inhibit TGF-a and amphiregulin expression, as shown by Sizemore et al (23). In support of this hypothesis, Noorgaard et al (24,25) reported that the FTI L744,382 decreases levels of TGF-a in mammary cystic fluid and inhibits the growth of mammary tumors in MMTV-TGF-a transgenic mice.…”
Section: Introductionmentioning
confidence: 99%